A nova ordem econômica nos contratos de arrendamento rural e parceria rural - Teodoro, Pedro Pereira (2011)
This monograph deals with land contracts and focuses on its adaptation under the new rural economy. To this end, the paper is divided in two parts. The first one presents the main issues concerning agricultural contracts, with focus on its legal and economic context, its autonomy and the application of the social and environmental function of contracts. In the second part, the issues previously characterized are discussed focusing exclusively on rural leases and rural partnership. Its current problems are pointed out based on doctrinal and jurisprudential conclusions